Applying the ADA Designing for The Americans with Disabilities Act Standards for Accessible Design in Multiple Building Types - Rhoads, Marcela Abadi (Wiley, 2013)
"By showing how the Americans with Disabilities Act Accessibility Guidelines (ADAAG) has been applied in various contexts and building types, this illustrated book helps readers quickly understand the requirements of the ADAAG. Building types covered include healthcare facilities, elementary schools, hospitality facilities, office buildings, college and university facilities, retail and mixed-use facilities, performing arts facilities, and senior living. The author will note both new construction and renovations. The author, an architect, consults regularly on accessibility issues for clients including design professionals, building owners, and facility managers"--